607 A Career in Neurosurgery: Perceptions and the Impact of a National SBNS/NANSIG Neurosurgery Careers Day. (19th August 2022) - Solomou, G; Venkantesh, A; Patel, W; Chari, A; Mohan, M; Bandyopadhyay, S; Gillespie, C; Mendoza, N; Watts, C; Jenkins, A
Abstract: Entrance to neurosurgical training is highly competitive. Without advice and opportunities, talented individuals may be dissuaded from applying. The Neurology and Neurosurgery Interest Group organised the 9th Annual Careers Day in Neurosurgery every year. Our objective was to assess the overall utility of a neurosurgery careers day and the perceived factors that attract and detract from the speciality. 18-item pre-conference post-conference questionnaires were disseminated electronically to conference attendees. Questions aimed to capture: i) baseline demographics; ii) previous experience and exposure in neurosurgery; iii) interest in neurosurgery; iv) understanding training and a career in neurosurgery; v) perceived factors of attraction and dissuasion of neurosurgery; and vi) perceived value, quality and educational purpose of the conference. In total, 77 delegates attended. 19/77 did not have a formal neurosurgical rotation during medical school, but almost half had gained neurosurgical experience. The careers day increased knowledge of the neurosurgical application process (median Likert score 3/5 to 4/5), duration of training (72.7% to 88.3%), and desire to pursue a career in neurosurgery (75.3% to 81.8%). The most common factors attracting delegates to neurosurgery were interest in neuroanatomy (80.5%, n=62) and practical skills (64.9%, n=50). Dissuasive factors were competition to entry (64.9%, n=50) and long working hours (40.3%, n=31). Almost all would recommend the event to a colleague (94.9%, n=73). Undergraduate exposure to neurosurgery is limited. Neurosurgery careers days increase awareness and understanding of the application process and improve interest in a selected cohort. The factors attracting applicants to neurosurgery remain practical links to anatomy and direct impact on patients.